2(2p-3)=36-2p

Simple and best practice solution for 2(2p-3)=36-2p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2p-3)=36-2p equation:


Simplifying
2(2p + -3) = 36 + -2p

Reorder the terms:
2(-3 + 2p) = 36 + -2p
(-3 * 2 + 2p * 2) = 36 + -2p
(-6 + 4p) = 36 + -2p

Solving
-6 + 4p = 36 + -2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2p' to each side of the equation.
-6 + 4p + 2p = 36 + -2p + 2p

Combine like terms: 4p + 2p = 6p
-6 + 6p = 36 + -2p + 2p

Combine like terms: -2p + 2p = 0
-6 + 6p = 36 + 0
-6 + 6p = 36

Add '6' to each side of the equation.
-6 + 6 + 6p = 36 + 6

Combine like terms: -6 + 6 = 0
0 + 6p = 36 + 6
6p = 36 + 6

Combine like terms: 36 + 6 = 42
6p = 42

Divide each side by '6'.
p = 7

Simplifying
p = 7

See similar equations:

| 8(8x-1)+4(1+8x)=-4 | | -23=6x+2 | | 16x^2-72x+75=0 | | 9x+6=-36 | | 32=-6x+2 | | 69-1=9+20 | | 17x+20=16x+20 | | 10x+1=9x+12 | | -23=6*4+2 | | x+77+x+62=45 | | 32=-6*-5+2 | | 58=-6*-7+2 | | 2x-5=4.4 | | 68=-6*-10+2 | | 4x-10-3x-(x-7)= | | 4(8b-5)=-4b+16 | | 7x-4+30=5+10x | | 7x-6+3x-9+5x=180 | | 56+x+85=42 | | X+15=8.4 | | x/2+1/4=3/4 | | x-(3x-5)+(6x+14)=180 | | 2y+5x=13 | | 8(4n+7)=-34+2n | | 3x+6x=981 | | 2x+44=12x | | -27+8n=5(2n-3) | | x^2+4x-4=-9 | | 9x-2+48=11x+22 | | -8(-4-5a)=32-5a | | x-y-2z=2 | | 110-2x=180 |

Equations solver categories